2013
DOI: 10.1177/230949901302100312
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic Prophylaxis for Hip Fracture Surgery: Three-Dose Cefuroxime versus Single-Dose Gentamicin and Amoxicillin

Abstract: The single-dose gentamicin and amoxicillin regimen was associated with a lower C difficile 'infection' rate.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 10 publications
0
9
0
Order By: Relevance
“…Thirty‐six studies were included in the final synthesis: one thesis and 35 journal articles . The 36 studies included 11 randomized controlled studies (two crossover designs), 18 cohort studies, one retrospective survey, three pharmacokinetic and three quasiexperimental studies.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirty‐six studies were included in the final synthesis: one thesis and 35 journal articles . The 36 studies included 11 randomized controlled studies (two crossover designs), 18 cohort studies, one retrospective survey, three pharmacokinetic and three quasiexperimental studies.…”
Section: Resultsmentioning
confidence: 99%
“…Reported adverse events are summarized in Table . Twenty‐three , of the 36 included studies, reported adverse events in the gentamicin arm of their study although not all adverse events were related to gentamicin. Pons et al .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…difficile infection, the magnitude of reduction ranged from two to six fold. [1013] Three of these studies were designed to demonstrate the effectiveness of new antibiotic policies recommending narrower-spectrum antibiotics and lower doses [1113], the most restrictive of which allowed for a single-dose of gentamicin and amoxicillin antibiotic prophylaxis regimen for hip hemiarthroplasty in surgical patients [13]. …”
Section: Introductionmentioning
confidence: 99%